Mustika Ratu's Business Rejuvenation Strategy in Overcoming Market Stagnation and Industrial Competition - Muh. Ihsan Said Ahmad; Agung Zulfikri; Syamsu Rijal (Westscience Press, 2023)
This research examines Mustika Ratu's business rejuvenation strategy in overcoming market stagnation and industry competition within the beauty and wellness industry. The study conducts a comprehensive market analysis and explores the implementation of various rejuvenation strategies, including product innovation, market expansion, marketing campaigns, and strategic partnerships. The evaluation of these strategies reveals positive outcomes in terms of increased customer satisfaction, expanded market reach, and improved brand perception. The findings highlight the importance of continuous adaptation, innovation, and targeted marketing efforts in revitalizing a business and regaining a competitive edge. The implications of the research suggest the need for ongoing product development, exploration of international markets, digital marketing enhancements, strategic collaborations, and continuous monitoring of consumer preferences. Overall, Mustika Ratu's successful rejuvenation serves as a valuable case study for businesses in similar industries facing market stagnation and intense competition.